Latent profile analysis of Eysenck’s personality dimensions and psychological constructs in university students - Pan, Lin-Ling; Zhou, Si-Ran; Chen, Guan-Zhao; Ke, Yue-Dan; Huang, Zi-Ye; Wu, Yu-Wei; Yan, Wen-Jing (Frontiers in Psychology, 2024)
Background The exploration of personality traits in relation to psychological constructs has become increasingly relevant in understanding the mental health of university students (the emerging adulthood). Studies have focused on how dimensions intersect with various psychological parameters. Aim The study aims to identify distinct personality profiles among university students based on Eysenck’s personality dimensions and investigate how these profiles differ across psychological constructs. Method A quantitative methodology was utilized, involving 708 university students from Wenzhou and Nanjing in China as participants. The research employed the Eysenck Personality Questionnaire along with other psychological measures. Latent Profile Analysis was applied to categorize the participants into distinct personality profiles. Results Four distinct personality profiles emerged: ‘The Reserved Analyst,’ ‘The Social Diplomat,’ ‘The Unconventional Pragmatist,’ and ‘The Impulsive Truth-Teller.’ Significant differences were found among these profiles on various psychological constructs. ‘The Social Diplomat’ exhibited the most adaptive psychological profile, with higher cognitive reappraisal (F = 45.818, p < 0.001, η2 = 0.163), meaning in life (F = 17.764, p < 0.001, η2 = 0.070), and positive coping (F = 40.765, p < 0.001, η2 = 0.148) compared to other profiles. Conversely, ‘The Reserved Analyst’ showed higher intolerance of uncertainty (F = 13.854, p < 0.001, η2 = 0.056) and state anxiety (F = 26.279, p < 0.001, η2 = 0.101). Conclusion This study enriches the understanding of personality traits in relation to psychological constructs within the context of university student populations. By identifying distinct personality profiles, it lays the groundwork for developing tailored mental health strategies that cater to the specific needs of different student groups.